A comprehensive methodological framework for improving security and efficiency of port container logistics. (1st October 2008) - Iakovou, Eleftherios; Georgiadis, Patroklos; Vlachos, Dimitrios
As ports have become key logistics nodes in global chains, port management of container operations has been experiencing radical changes. Moreover, the ramifications of the associated policy-making expand well beyond their own boundaries. The challenging managerial environment is further exacerbated by security concerns and regulations that have gained increased importance during the past years. In this work, we present a System Dynamics simulation-based methodological framework for the modelling and analysis of strategic decision-making for port containers management tackling the issues of security and efficiency. More specifically, we investigate the implications of alternative inspection policies on port system performance, while taking into account the interdependencies of the inspection process with the capacity planning of port operations. Finally, we demonstrate the applicability of the developed methodology on a major port of Greece.